KONSEP KEADILAN (IUSTITIA) PERSPEKTIF ST. THOMAS AQUINAS DAN RELEVANSINYA BAGI PEMAKNAAN SILA V PANCASILA - Giovanni Aditya Arum (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2019)
In principle justice touches the human nature as social animal. The discourse of justice has become an important theme in social and political philosophy all the times. St. Thomas Aquinas is one of the philosophers who pays much attention on this theme. In Summa Theologiae, he spent a lot of pages to explain justice as one of the cardinal virtues. Inspired by Aristotle, he defined justice as “a habit whereby a man renders to each one his due by a constant and perpetual will.” This essay wants to explain the discourse of justice according to St. Thomas Aquinas and to compare it with the concept of justice in fifth principle of Pancasila. The writter uses the relevancy study to get the convergency idea between two different ideas of justice. This essay will explore both concept of justice by St. Thomas Aquinas and Pancasila perspective. There are at least some convergency ideas between those two. But the pressure point is the concept of bonum commune. Pancasila as the Philosophische Grondslag of Indonesia as like as St. Thomas Aquinas’ idea of justice emphasizes the common good (bonum commune) as the very end of Indonesia nation. Reflecting on these convergency ideas, we can find some relevant discourses concerning justice in socio-political life of Indonesian people, i.e: law, politic, and religion. In the end of this essay, the writer gives a critical thought to the tendency of the liberalism pathology in social life